Immobilization of glucoamylase on silica gel for the hydrolysis of cassava starch - Bajo, Lydia M.; Castillo, Eugenia M.; Espino, Teresita M. (2000)
Glucoamylase from Bacillus sp. AMI was immobilized on either silica gel, CaCO₃, celite, or dowex support by physical adsorption. The first showed the highest capacity for adsorption, the next two intermediate, and the last the least.

Optimum pH of the immobilized form of the enzyme was 5.5, its optimum temperature 55 C. The Michaelis-Menten constant, Kₘ, was 0.0032 mM for the immobilized form and 0.0038 mM for the free form. The Vₘₐₓ was 4.97μmol min1 and 4.75 μmol min⁻¹ for the free and immobilized forms, respectively. The Vₘₐₓ of the two forms did not vary significantly. Ca²⁺ and Zn²⁺ ions significantly activated but L-cystine, EDTA and HgCl₂, inhibited the AMI glucoamylase. The immobilized form was found to be stable on storage, on repeated use, and toward chemical denaturants (0.80 M urea, 2% SDS and 0.50M GdmCl).

With cassava starch as substrate, the degree of hydrolysis by the enzyme was higher by 33.33% in its immobilized than in its free form.

The apparent molecular weight of glucoamylase by gel filtration chromatography is 55,900 Da; the carbohydrate content is 0.45%.
Keywords: Cassava; Organic chemistry research